A matemática nos truques, advinhações e enigmas - Sousa, Eryvelton Alves (2014)
This paper discusses mathematical problems known as tricks, riddles or puzzles, in order to show the teachers and students with the beauty that can be found in mathematics. It is through less routine situations we seek to foster in students a mathematician. We also present a brief pedagogical foundation based on the needs of the teacher teaching mathematics to know how to approach situations and problems during a course, and not a theoretical axiomatic exposition of content but so that they can ensure the correct interpretation of the problems listados.O goal was to gather a list of issues to support and motivate students to become more interested in mathematics using a subtle side that is often neglected in the teaching of mathematics in elementary and middle school.